Marketing digital en el incremento de las ventas en la Empresa Salud S.A, Guayaquil, provincia del Guayas - Chica Macías, Brenda Raquel (2023)
Technology represents an important ally for marketing, which is why, currently, professionals in this administrative area have developed marketing plans using digital spaces, replacing conventional ones, due to lower costs and high existing demand in them, by internet users who daily browse these sites on the Internet platform. For this reason, the present investigation that analyzed the problem of restrictions in the customer acquisition process, due to the reforms in the Data Protection Law, had the objective of establishing digital marketing in increasing the sales of the company Salud S.A. The quantitative, descriptive, field methodology was applied, with the application of the survey to a sample of 368 users. The results showed that, in order to take advantage of the latent opportunity in the market, a digital marketing plan must be developed, with the design of an Instagram account and the posting of paid and unpaid advertising, which has a budget of $8,250.00 and you can continuously improve the process of attracting users in the company. In conclusion, if a digital marketing plan is established, then sales can be increased in the company Salud S.A.